Analisis Desain Logistik Packaging Telur Guna Mengurangi Produk Defect Telur Ayam - Alfianto, Abimanyu; Toro, Bakti Wijian; Gymnastiar, Ahmad Alisson; Amrulah, Muhammad Daffa; Yuliawati, Evi (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2024)
Logistics plays an important role in supplying the farming industry, including ensuring the quality of the products produced to the consumer. In the poultry egg industry, efficient and efficient logistical management can be a key factor in the success of reducing defective products. Defective products such as cracks, breaking eggs or poor quality at the time of distribution can cause considerable economic losses and reduce consumer confidence in such products. Good logistics design covers many different aspects, ranging from choosing the right packaging, safe transportation, careful handling and proper storage.Chicken eggs are easily damaged, fragile products and their quality declines rapidly during transportation and storage. The use of egg tray is considered necessary primarily to minimize damage to eggs during transportation. Packaging chicken eggs often uses baskets, plastic egg containers, plastic stamps and folding boxes that do not protect eggs from damage. Poultry egg packaging has a very important function but many merchants who don't sell eggs without a good packaging are at risk of damaging. Eggs. During the sale to the public, producers often pack eggs in plastic packages that do not protect the eggs a hundred percent. With the value engineering approach covers minimizing unnecessary costs without reducing the quality of the product. The advantage of this is that egg entrepreneurs can cost-efficient logistics without reducing the value of the product. In addition to considering the function of the packaging, entrepreneurs should also consider the attractiveness of the product as something inseparable from the consumer reference, as it is a driving force for the purchase of chicken egg products.